KEMAMPUAN FAKTOR AKUNTANSI DAN NON AKUNTANSI DALAM MEMPREDIKSI BOND RATING - Rusfika, Rusfika; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the ability of accounting and non-accounting factor in predicting the bond ratingto the non-finance companies. The samples are non-finance companies which are listed in Indonesia Stock Exchange(IDX) during 2010-2013 periods which are rated by PT.Pefindo. The samples of the research have been selected byusing purposive sampling method. 48 samples of bonds with 192 pooling of 16 companies have been obtained.Hypothesis test has been done by using logistic regressions analysis. Based on the result of the logistic regressionsanalysis with its significance level is 5% has proven that: 1) Profitability, solvability, liquidity and bail bond havepositive and significant influence to the bond rating, 2) Productivity, bond age and auditorâs reputation haveinsignificant influence to the bond rating.Keywords: Bond Rating, Accounting Factor, Non-Accounting Factor